ACADEMIC SUPERVISION TO IMPROVE TEACHER'S CAPABILITY IN ARRANGING ASSESSMENT ADMINISTRATION THROUGH DOCUMENT REVIEW AND GUIDANCE DURING THE COVID-19 PANDEMIC - Makmur Makmur (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aims to determine how the planning, implementation, and follow-up steps of academic supervision by supervisors to improve teacher competence in preparing assessment administration. This research is action research. The data analysis technique used in this study is a comparative descriptive analysis technique and quantitative data. The results of the study indicate that academic supervision can improve teacher competence in arranging assessment administration. Teacher competence in the initial conditions, cycle I and cycle II showed the value of the teacher's ability in the preparation of the initial learning assessment administration with an average of 69.11, in the first cycle 74.78 and finally in the second cycle with an average of 78.11. teachers in the preparation of learning assessment administration from cycle to cycle. The amount of increase is 5.67 from the initial condition to the first cycle and 3.33 from the first cycle to the second cycle. The conclusion from the research is that the implementation of academic supervision can improve the ability of teachers in preparing assessment administration.